Functional and anatomical outcomes following cartilage myringoplasty - Mohan, Nidhi S.; Mushannanavar , Annapurna S.; Gadag, Raveendra P.; Dandinarasaiah, Manjunath (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: Myringoplasty using cartilage graft is being popular in recent years because of its better graft uptake and optimal hearing outcome. Thickness plays an important role in achieving optimal hearing outcome and although studies have shown 0.5 mm thickness to give better hearing results, concrete studies are lacking. Methods: A prospective study was conducted in the department of otorhinolaryngology at a tertiary-referral-hospital in North-Karnataka; India between January-December 2019, on 25 patients of chronic otitis media; mucosal inactive or quiescent with conductive hearing loss and intact ossicular chain who underwent cartilage myringoplasty using conchal cartilage of 0.5 mm thickness. Follow-up was done at 3, 4½ and 6 months postoperatively to assess graft uptake. Hearing assessment was performed at the end of 6 months postoperative period with pure-tone audiometry. Results: The preoperative mean pure tone average was 33.64±9.42 dB which improved to 22.56±7.41 dB at 6 months. At 3 months and 4½ months, there were 21casess (84%) of complete graft uptake, 3 cases of partial graft uptake (12%) and one case of total graft rejection (4%). Whereas, at 6 months postoperative period complete graft uptake was seen in 22 cases (88%) with 1 case of total rejection (4%) and 2 cases of partial uptake (8%). Conclusions: Cartilage myringoplasty using 0.5 mm thickness conchal cartilage offers good hearing outcome in addition to significant graft uptake. As the conchal cartilage can be easily harvested from the site of incision for the surgery it can be an important primary alternative to temporalis fascia.